Can child-care subsidies reduce poverty? Assessing the Korean experience using the Levy Institute Measure of Time and Income Poverty - Ajit Zacharias; Thomas Masterson; Kijong Kim (Levy Economics Institute of Bard College, 2014)
In partnership with the Korea Employment Information Service, Senior Scholar Ajit Zacharias and Research Scholars Thomas Masterson and Kijong Kim investigate the complex issues of gender, changing labor market conditions, and the public provisioning of child care in Korea using the Levy Institute Measure of Time and Income Poverty (LIMTIP), an alternative measure that factors in both time and income deficits in the assessment of poverty. Since the 1997 Asian financial crisis, lifetime employment and single-breadwinner households have given way to increased job insecurity, flexible work arrangements, and rapid growth in dual-earner households in Korea. Add to these factors rising labor force participation by women but little change in the highly unequal division of household production, and many women effectively face a double shift each day: paid employment followed by a second shift of household production. Recognizing the implications of the heavy burden of care work for women's well-being and employment, Korea introduced public child-care provisioning, via a voucher system for low-income families, in 1992 (the program became universal in 2013). This study analyzes the impact of the voucher program on reducing time and income poverty, and reassesses the overall level of poverty in Korea. While it reveals a much higher level of poverty than official estimates indicate - 7.9 percent versus 2.6 percent - due to time deficits, the outsourcing of child-care services reduced the LIMTIP rate from 7.9 percent to 7.5 percent and the number of "hidden poor" individuals from two million to 1.8 million. While these results show that the problem of time poverty in Korea extends beyond child-care needs, the impact of public provisioning through the voucher program clearly has had a positive impact on families with children.
Keywords: 330